2022
DOI: 10.9744/jmk.24.2.105-117
|View full text |Cite
|
Sign up to set email alerts
|

Herd Instinct Bias, Emotional Biases, and Information Processing Biases in Investment Decisions

Abstract: The evolution of information during the COVID-19 pandemic has altered how investors invest. Investments can be made easily on a variety of digital platforms that provide easy access to information in investment decisions. Information media is expanding to promote investment decision making, boosting the rise and development of investor financial behavior bias. This study attempts to fill a knowledge gap in behavioral finance by concentrating on behavioral biases such as Herd Instinct Bias, Emotional Biases, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…However, studies on confirmation biases have been limited in Nepal. The study by Armansyah (2022) suggested that confirmation bias had a significant impact on the investment decisions of Indonesian investors. Most Nepalese research on behavioral finance has found a significant impact of overconfidence bias on investment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on confirmation biases have been limited in Nepal. The study by Armansyah (2022) suggested that confirmation bias had a significant impact on the investment decisions of Indonesian investors. Most Nepalese research on behavioral finance has found a significant impact of overconfidence bias on investment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the work by Winston as cited above, Galily [32] emphasizes the "automatic responses" of bodies driven by patterns that have developed over many generations, a definition that serves well for our purposes. Scholars often decide to use latent variables to estimate the prevalence of instincts [33,34], as instincts are strongly interwoven with the subconscious [35]. Particularly in quantitative settings, it is unrealistic to unveil respondents' instincts in a direct, meaningful way within a survey.…”
Section: Stated Intentionmentioning
confidence: 99%
“…Additionally, the media can play a role in challenging subjective norms that may not align appropriately. Armansyah (2022) has highlighted the significance of information processing bias, particularly in the context of advancements in information technology and communication media, and its substantial contribution to investment decision-making. Hasanudin (2023) explained that the availability of information from social media has a considerable influence on investment decisions among millennials.…”
Section: Information Media In Moderating Subjective Norms and Sharia ...mentioning
confidence: 99%